Application of nano emulsion method in a methanol powered diesel engine. (1st May 2017) - Soni, Dinesh Kumar; Gupta, Rajesh
Abstract: Demand of methanol-blended diesel fuel is increasing to compensate the use of diesel fuel in transportation purpose despite of their own drawbacks of emission like other petroleum fuels. One of the major drawbacks is high NOx emission. The nitrogen oxides (NOx ) emission from methanol-blended diesel engine is not only harmful for the environment, but also affects the life of world population slowly. Present research is to reduce NOx emission from a methanol-blended diesel engine. The methanol-blended diesel engine was used in the experiments. In the investigation, diesel fuel is used with three blends of methanol-blended diesel fuel in the proportion of 0%, 10%, 20% and 30% respectively, viz, diesel, D + M10, D + M20 and D + M30. Results indicated that, D + M30 blend produced lower emissions than other blends, but NOx emission was still higher. Therefore, it was selected as an optimum blend. To bring this under control, water nano emulsion method was applied to the optimum blend. The optimum blend was treated by WNE method in the percentage of 5%, 10% and 15% while keeping the optimum blend ratio constant. The results revealed that, NOx emission was reduced significantly by the use of 15% water nano emulsified blend, whereas other emission were increased marginally. Highlights: The high NOx emission from methanol blended diesel engine is a major problem. No need of any physical modification in the engine with WNE method. WNE method is used to reduce NOx emission from an optimum blend of methanol blended diesel engine. The CO and HC emission are increased marginally. The high oxygen concentration of methanol fuel restricts formation of CO and HC particles.